KNEWTON ANALYTICAL REVIEW AS A PLATFORM FOR PERSONALIZATION OF LEARNING CONTENT - Nosenko, Юлія (Journal of Information Technologies in Education (ITE), 2020)
The article analyzes the theoretical basis of Knewton adaptive learning platform, identifies the benefits and prospects for its use in the educational process.The Knewton platform, developed by the company of the same name (USA), became one of the first adaptive learningplatforms in the world and is now the undisputed world leader in this context. It provides continuous adaptability, constantly accumulating data about each student and properly building an individual learning trajectory, forming appropriate recommendations in real time. Knewton itself does not develop ready-made courses, but instead provides a platform that offers developers certain algorithms for adapting educational content.The theoretical basis of the Knewton platform is a number of models and approaches, including: item response theory, probabilistic graphical models, hierarchical agglomerative clustering.Among the Knewton tools that provide personalization of learning, we consider such as knowledge graph, constant reinforcement, learning curves, student learning profile, network effects.The main advantages of Knewton for students include: instant "feedback", collaboration, gamification. The advantages for teachers are meeting the various needs of students, monitoring the progress of the whole class, monitoring the progress of an individual student, improving the content of educational programs.General recommendations for the development of an adaptive course based on Knewton (on the example of the Alta) are given. The models of potential application of the Knewton platform are characterized: "face to face", "rotation", "flex", "online laboratory", "self-blend", "online user".Given that the practical experience of adaptive learning systems, both in Ukraine and in the world as a whole, is quite small, we believe that it is important to consider the theoretical foundations of these technologies, critically assess their advantages and disadvantages, and prospects for implementation and use. In the future, we plan to develop recommendations for teachers tocreate training courses based on the Knewton platform.